Geopolitics and empire the legacy of Halford Mackinder - Kearns, Gerard (Oxford Oxford University Press, 2009)
Geopolitics and Empire examines the relations between two phenomena that are central to modern conceptions of international relations. Geopolitics is the understanding of the inter-relations between empires, states, individuals, private companies, NGOs and multilateral agencies as these are expressed and shaped spatially. This view of the world achieved notoriety as the scientific basis claimed by Nazi ideologists of global conquest. However, under this or another name, similar sets of ideas were important on both sides of the Cold War and now have a renewed resonance in debates over the New World Order of the so-called Global War on Terror. Geopolitics is a way of describing the conflicts between states as constrained by both physical and economic space. It makes such conflicts seem inevitable.
Includes bibliographical references (p. [297]-[335]) and index.
Keywords: Mackinder, Halford John, 1861-1947.